Re-evaluation of historic putative caimanine material from the lower Palaeocene Salamanca Formation in Patagonia (Argentina) - Tobias Massonne; Felix J. Augustin (Fossil Record)
The fossil record of caimanines is characterised by two important periods: the first in the early Palaeocene and the second in the late Miocene. While numerous well-preserved taxa are known from the latter period, the incompleteness of fossils from the Palaeocene presents a significant challenge to understanding the evolution of Caimaninae. Here, we re-describe material collected by the German palaeontologist Friedrich von Huene in 1924 from outcrops of the Salamanca Formation at Cap Peligro in Patagonia, Argentina. The material consists of several isolated bone fragments (i.e., a frontal, parietal, dentary and angular, as well as seven vertebrae, three femora, four metatarsals and two osteoderms), currently housed in the Palaeontological Collection of the University of Tübingen in Germany. The size differences between the bones clearly indicate that they belong to different individuals; due to a lack of overlapping elements, it is unclear if they all belong to a single or, instead, to several distinct species. A comparison with recently described caimanines from the Palaeocene and Eocene of South America (i.e., Eocaiman cavernensis, E. itaboraiensis, E. palaeocenicus, Necrosuchus ionensis and Protocaiman peligrensis) shows that the material presented herein differs in lower jaw morphology from all other species (except P. peligrensis for which the lower jaw is unknown), but that the skull bones show a great similarity to those of P. peligrensis. The absence of overlapping skull material from all other species and of lower jaw material of P. peligrensis leads to the cautious assignment of the herein presented material to Caimaninae indet.